In Situ Monitoring the Role of Working Metal Catalyst Nanoparticles for Ultrahigh Purity Single‐Walled Carbon Nanotubes. (22nd May 2013) - Chen, Tian‐Chi; Zhao, Meng‐Qiang; Zhang, Qiang; Tian, Gui‐Li; Huang, Jia‐Qi; Wei, Fei
<x xml:space="preserve">Abstract</x> The high‐end applications of single‐walled carbon nanotubes (SWCNTs) are hindered by the existence of large amount of impurities, especially the graphene layers encapsulating metal nanoparticles (metal@C NPs). The role of working metal catalysts during chemical vapor deposition (CVD) growth and post purifications by oxidation are not yet fully understood. Herein, the in situ monitoring the role of working metal catalyst NPs for ultrahigh purity SWCNTs by CVD growth and CO2 purifications is carried out in an online thermogravimetric reactor attached with a mass spectrometer. The growth of SWCNTs almost stops after the initial 2 min, then, the mass increase of the samples mainly originates from the metal@CNP formation. Therefore, high‐purity SWCNTs (98.5 wt%) with few metal@CNPs can be available by 2 min CVD growth. Furthermore, CO2 oxidation of the SWCNTs is also investigated in a thermogravimetric reactor. The oxidation of graphene layers surrounding the metal NPs and the SWCNTs occurs during distinct temperature ranges, which is further demonstrated by the significant differences among their oxidation activation energies. Ultrahigh purity of SWNCT with a carbon content of 99.5 wt% can be available by a CO2‐assited purification method. The in situ study of the CVD growth and CO2 oxidation of SWCNTs provides the real time information on the working catalyst during reaction and the reactivity information of metal@CNPs and SWCNTs under an oxidizing atmosphere. The success for the preparation of high‐purity SWCNT lies in the efficient growth of SWCNTs with a low amount of nanocarbon impurities and partial oxidation of metal@CNPs by catalytic CO2 oxidation with proper operation parameters.